La necro-lógica de la violencia sociopolítica en la primavera de 1936 - Eduardo González Calleja (Mélanges de la Casa de Velázquez)
Political order was one of the major problems faced by the Second Republic from its outset, and a decisive element for an understanding of the fate of the democratic regime in the drama of the summer of 1936. This paper proposes a statistical evaluation of socio-political violence involving deaths in Spain between 16 February and 17 July of that year. To that end the author has compiled a data base listing victims individually and established the following classification criteria: place of occurrence, province, date, government responsible, type of violent incident, type of weapon used, and profession and political affiliation and age of the victims and of the persons reputedly responsible for their deaths.